PELATIHAN PENGGUNAAN MICROSOFT WORD PADA SISWA/SISWI DI MIS AL-ISLAMIAH BATU PUTIH, DESA ALILA TIMUR KABUPATEN ALOR, PROVINSI NTT - Isah E Lengmani; Maria Ailabui; Mikae Laaduka; Muhammad A. Nenu; Kornelius Gegung; Jon Idrison Molina; Julminggu J. Selly (Intimas, 2026)
The rapid development of information technology requires elementary school students to possess basic computer and word-processing skills. Microsoft Office Word is widely used in educational and administrative activities; however, initial observations revealed that many students at MIS Al-Islamiah Batu Putih lacked basic knowledge of this application. This community service activity aimed to improve students’ digital literacy and skills in using Microsoft Office Word 2016 through a structured training program. The methods included demonstrations, hands-on practice, guided assistance, question-and-answer sessions, and skill evaluation. The training was conducted over two days and involved students from grades I to VI. The results indicated a significant improvement in students’ ability to operate laptops, type and format documents, create tables, insert images, and save files correctly. Furthermore, the program enhanced students’ self-confidence and interest in technology-based learning. Therefore, this training proved effective in strengthening basic information technology skills among elementary school students.